Enhancing methylene blue removal: synthesis, characterization, and performance evaluation of chemically activated carbon adsorbents - Hamad, Hamad Noori; Idrus, Syazwani; Yusuf, Badronnisa; Jamali, Nur Syakina (Elsevier, 2024)
In response to the pressing environmental issue of efficiently removing methylene blue (MB) from aqueous solutions, this study introduces a novel approach utilizing activated carbon (AC) synthesized via a two-stage activation process involving zinc chloride (ZnCl2) and ammonium sulfate ((NH4)2SO4). SEM analysis confirms the development of a porous structure at distinct activation temperatures (700 °C and 260 °C), while comprehensive characterizations, including FTIR, BET, TGA, CHNOS, and XRD, provide valuable insights into the structural and chemical properties of the synthesized AC. Optimization of the activation process at the second stage using (NH4)2SO4 yields a remarkable surface area of 939.63 m2/g, crucially enhancing functional groups such as Hydroxyl (O-H) and Carbonyl (C[dbnd]O). The experimental design involved optimizing various parameters, including contact time (0–180 mins), initial concentration (200–500 ppm), temperature (25–55 °C), pH (4−10), and adsorbent dosage (0.4–0.65 g). Batch adsorption optimization experiments demonstrate exceptional efficiency, achieving 99.91 % MB removal and a 90.827 mg/g capacity. Furthermore, Langmuir and second-order kinetic model fitting indicate favorable adsorption behavior, supported by thermodynamic analysis revealing an endothermic process. Notably, AC exhibits excellent regenerative potential over four cycles, emerging as a promising candidate for advancing water purification practices; the modified AC achieves WHO standards for MB removal in drinking water.